An Evaluative Study on Organizational Culture and its Impact on Strategic Leadership in it and ITES Industries in Delhi NCR - Dr. B. S. Hothi (International Journal of Advanced Science and Technology, 2020)
This study is an attempt to evaluate the role of organizational culture and its impact on strategic leadership in IT and ITES industries in Delhi NCR. The study assumes that organizational culture would have an impact on strategic leadership in IT and ITES industries in Delhi NCR. The related dimensions like work related factors, personal factors, work life balance, ESOP would be taken in to consideration. The leadership influencing factors are determined and its role on organizational culture and its impact on strategic leadership would be investigated in this study. The type of organizational culture which is prevalent in IT & ITES industries would be ascertained by having an organizational cultural framework assessment from 51 types of most prevailing organizational cultures. After knowing the specific organizational culture prevailing in IT and ITES industries in Delhi NCR, the study would determine the impact of organizational culture on strategic leadership. This study is attempted for the first time as empirical, quantitative study using questionnaire, focus group discussion & interview conducted with managers, middle level manages and senior level managers of IT and ITES industries in Delhi NCR. It is expected that through this study it would be concluded that organizational culture has positive impact on strategic leadership in IT and ITES industries in Delhi NCR.